Microbial Contributions to Soil Health and Crop Yield in Organic Farming Systems - Yovita, Yovita; Lek, Siri; Kiat, Ton (Research of Scientia Naturalis, 2025)
Soil health is a critical component of sustainable agriculture, particularly in organic farming systems. Microbial communities play a vital role in maintaining soil quality and enhancing crop productivity. Understanding these contributions is essential for optimizing organic farming practices. This study aims to investigate the specific roles of microbial communities in promoting soil health and improving crop yield in organic farming systems. By examining various microbial interactions and their effects on nutrient cycling, the research seeks to identify key factors influencing agricultural productivity. A field study was conducted on several organic farms, where soil samples were collected and analyzed for microbial diversity and activity. Crop yield data were obtained from participating farmers, and statistical analyses were performed to assess the relationships between microbial metrics and crop productivity. Findings indicate that higher microbial diversity and activity correlate positively with improved soil health indicators, such as organic matter content and nutrient availability. Additionally, crops grown in soils with robust microbial communities demonstrated significantly higher yields compared to those from less diverse microbial environments. This research underscores the importance of microbial contributions to soil health in organic farming systems.